IMPLEMENTASI EVALUASI PEMBELAJARAN AQIDAH AKHLAK PADA KURIKULUM MERDEKA DI MADRASAH ALIYAH NEGERI - Fahrul Ashari; Rahmat; Atika Putri Pratiwi Sihaloho (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of learning evaluation is very important in the education process because educators need in-depth information about students in cognitive, affective, and psychomotor aspects. Evaluation is one of the key factors that supports educational success. This study aims to analyze the implementation of Aqidah Akhlak learning evaluation in the Merdeka Curriculum at Madrasah Aliyah Negeri, as well as to analyze supporting factors, inhibiting factors, and implementation solutions. This research uses a case study approach with data collection techniques through interviews, observations, and documentation. The research informants include the head of the madrasah, the vice principal for student affairs, Aqidah Akhlak teachers, and students who are directly involved in the implementation of learning evaluation. Research results show that the implementation of assessment in Aqidah Akhlak learning in the Merdeka Curriculum includes diagnostic, formative, and summative evaluations. Supporting factors for implementing the evaluation include teachers' readiness and competence, valid instruments, adequate facilities and infrastructure, school support, learning media, students' honesty, follow-up on evaluation results, the Digital Madrasah Program, and the use of the SCOLA application. Hindering factors include teachers' lack of understanding, inappropriate instruments, low honesty and motivation among students, varying digital skills, limited devices, internet network issues, SCOLA application disturbances, and the need for further adaptation to the Merdeka Curriculum. The solutions implemented include training and workshops for teachers, creating a competency-based question bank, strengthening a culture of honesty, documenting and analyzing evaluation results, providing offline and paper-based evaluations, supporting technology use, applying engaging learning approaches, and mapping students' technology skills to optimize learning assessments.